A study protocol for an mHealth, multi-centre randomized control trial to promote use of postpartum contraception amongst rural women in Punjab, Pakistan - Xaher Gul; Waqas Hameed; Sharmeen Hussain; Ishaque Sheikh; Junaid- (BMC, 2019)
Abstract Background Provision of family planning services during the immediate post-partum phase is considered effective and cost-efficient for promoting healthy timing and spacing of pregnancies. This research aims to test the effectiveness of mobile phone-based interventions in promoting use of postpartum contraception. Moreover, it will also test the non-inferiority of text and voice messages compared to interactive phone-based counselling. Methods A three-arm, 10-month, multicentre, randomized controlled trial will be conducted at 15 social franchise (SF) health facilities in Punjab province of Pakistan. Pregnant women aged 15-44 years who are in their first or second trimester and have a mobile phone for their own use will be eligible to participate in this study. The participants will be randomly allocated to one of three study arms: a) voice and text messages; b) interactive telephone-based counselling; or c) control arm (no additional phone-based support). The intervention counselling module will be developed based on the Integrated Behaviour Model which was recently adapted, and tested for the family planning context in Pakistan. It will broadly cover birth-preparedness, importance of birth spacing, and postnatal care. The phone-based intervention aims to improve women's ability to use contraception by providing them with information about a range of methods, access to family planning methods through outlets such as Suraj SF providers, connecting them with MSS field health educators to help them reach the centres, motivation by re-enforcing the benefits of contraceptive use on women's quality of life, and dispelling myths and misconceptions about modern contraceptive methods. Risk differences will be used as the measure of effect of the intervention on the outcomes. Discussion The study findings will highlight effectiveness of mobile phone in raising awareness of maternal health and contraception, which in turn, is expected to be translated into increased proportion of: at least four antenatal visits, skilled birth or institutional delivery, postpartum contraceptive use, postnatal check-up, child immunization, and breastfeeding. Moreover, if the text and voice messages approach is proven to be non-inferior to interactive calls, it will provide evidence to making promotion of healthcare less resource intensive, and thereby contribute in improving the efficiency of the healthcare system. Trial registration This trial was prospectively registered with the Clinical Trials registry (NCT03612518) on August 2nd, 2018.